COVID-19: preguntas frequentes para huertas comunitarias: pasos para encargados de huertas y jardineros - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS)
This is the Spanish-language version of FSHN20-19/FS342: COVID-19 FAQ for Community Gardens: Steps for Garden Managers and Gardeners. Written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman (NC State University Extension), and published by the UF/IFAS Food Science and Human Nutrition Department, April 2020.